The cultural identity of contemporary metalworking in the Kingdom of Saudi Arabia according to Maurice Weitz’s critical reading - Alsqha, Shatha brahim; Al-Hudhali, Hilalh Jubeir (Journal of Humanities & Social Sciences, 2022)
The cultural characteristics of peoples are related to the components of life and society, and distinguish them from other peoples. The cultures depend on the economic and religious components of the countries and the customs and traditions that they carry and the extent of their impact on their cultural identity. The arts through the ages also express the culture of civilizations and their societies because of the contents that represent their cultural identity. Accordingly, the current research dealt with the field of cultural identity of metalworking in the Kingdom and its aesthetic components in a sample of the works of the contemporary Saudi artist. The research also aimed to identify the cultural identity, reveal the most important premises of cultural identity in the artwork, clarify the concept of metal works and the methods of its formation, and clarify the concept of Morris Weitz’s reading of critical analysis. The research followed the descriptive approach in identifying the concepts of cultural identity, the methods of forming works, clarifying the concept of critical reading of Morris Weitz, and the analytical approach by analyzing a sample of metal works by Saudi artists. The cultural identity premises are determined to build the artwork according to the artist’s vision and the artistic formations he presents.